AKTIVITAS DAN PEMECAHAN MASALAH MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI SMK - Magdalena Dhema; Adi Jufriansah (IKIP Siliwangi, 2021)
Vocational High School is a formal institution that creates more independent, creative, innovative, skilled, and responsible students in solving a problem. Graduates from vocational education are expected to be more competent in solving problems in the world of work. Students are also required to be more active in solving a problem. The research objective was to determine student activity and analyze mathematical problem-solving abilities in implementing mathematics learning using the Problem Based Learning model. The method used is to use a qualitative design. In this method, student activity is measure using the observation sheet, and the problem-solving ability test is carried out by following the steps of Polya's theory. The results showed that the overall student activity reached the excellent category. The general average problem-solving ability obtained an ideal classification, with the movement and moderate mathematical problem-solving ability of students achieving a reasonable variety and positively impacting all vocational students.